2008
DOI: 10.3324/haematol.10985
|View full text |Cite
|
Sign up to set email alerts
|

Anemia management in patients on peritoneal dialysis: efficacy and safety of epoetin  

Abstract: In a one-year, multicenter, open-label, uncontrolled trial, epoetin δ was given subcutaneously, 1-3-times weekly to peritoneal dialysis patients who had previously received an epoetin. Dose was adjusted to maintain hemoglobin at 10.0-12.0 g/dL. The primary endpoint was mean hemoglobin over weeks 12-24. Safety was assessed. Mean±SD baseline hemoglobin was 11.2±0.9 g/dL. Hemoglobin over weeks 12-24 was 11.6±1.1 g/dL. Adverse events were those expected in this patient population. No life-threatening adverse event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Epoetin delta has the same amino acid sequence as endogenous epoetin, and epoetin alpha and beta, but is synthesized in human cells [21], a process that may theoretically circumvent problems arising from species-dependent differences in protein folding or post-translational modifications. However, such theoretical problems have so far not become obvious and the pharmacodynamics and pharmacokinetics of epoetin delta are also similar to those of other recombinant human erythropoietins [22]; clinical trials indicate that it corrects renal anaemia in rHuEPO-naive patients [23] and can be used in the maintenance therapy of those already receiving epoetin alpha [24][25][26][27].…”
Section: New Esasmentioning
confidence: 99%
“…Epoetin delta has the same amino acid sequence as endogenous epoetin, and epoetin alpha and beta, but is synthesized in human cells [21], a process that may theoretically circumvent problems arising from species-dependent differences in protein folding or post-translational modifications. However, such theoretical problems have so far not become obvious and the pharmacodynamics and pharmacokinetics of epoetin delta are also similar to those of other recombinant human erythropoietins [22]; clinical trials indicate that it corrects renal anaemia in rHuEPO-naive patients [23] and can be used in the maintenance therapy of those already receiving epoetin alpha [24][25][26][27].…”
Section: New Esasmentioning
confidence: 99%
“…Unlike the available recombinant EPOs, epoetin delta is produced in a human cell line and therefore has a human-type carbohydrate structure. Subcutaneous as well as intravenous administration of epoetin delta is effective and well-tolerated for the treatment of anemia in CKD patients requiring peritoneal dialysis or hemodialysis [26,30]. To the best of our knowledge, this is the first study in which the erythropoietic effects of different dosing regimens of epoetin delta were investigated in a rat model of CRF.…”
Section: Discussionmentioning
confidence: 96%
“…Although anti-EPO antibodies have been found in 4 animals treated 3 times a week with epoetin delta, the development of these anti-EPO antibodies did not impair the erythropoietic response, neither was it dependent on the administered dose. Taken together, this is the first experimental study showing that epoetin delta, besides its successful effects in the management of renal anemia in CKD patients [23,24,25,26], is also effective in correcting anemia in the remnant kidney rat model. In addition to its hematopoietic effects, it has been hypothesized that EPO could influence the progression of renal impairment [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritonitis is a complication commonly associated with PD (16,17), and it is often the reason that patients switch from PD to HD (18). Studies of treatment with ESAs in patients on PD have reported peritonitis rates ranging from 9.3% to 29.4% (10,14,19).…”
Section: Discussionmentioning
confidence: 99%